2019
DOI: 10.12659/msm.915865
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant Blue G Inhibits Inflammasome Activation and Reduces Disruption of Blood–Spinal Cord Barrier Induced by Spinal Cord Injury in Rats

Abstract: Background Brilliant blue G (BBG) is a P2X7 receptor inhibitor that has been reported to improve spinal cord injury (SCI) in previous studies, but the specific mechanism has been unclear. In this study, we investigated the effects of BBG on inflammasomes and blood–spinal cord barrier (BSCB) permeability after SCI. Material/Methods The experimental rats were randomly divided into 3 groups: sham, SCI, and SCI+BBG. The expression of P2X7 and inflammasome-related proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…These findings were confirmed for the rat spinal cord [ 65 ] and extended for the rat parietal cortex [ 66 ]. Whereas in the former study BBG was used as a P2X7R antagonist, in the latter study the P2X7R antagonist A-804598 of higher selectivity was utilized.…”
Section: Mechanical Damage To the Cnsmentioning
confidence: 60%
“…These findings were confirmed for the rat spinal cord [ 65 ] and extended for the rat parietal cortex [ 66 ]. Whereas in the former study BBG was used as a P2X7R antagonist, in the latter study the P2X7R antagonist A-804598 of higher selectivity was utilized.…”
Section: Mechanical Damage To the Cnsmentioning
confidence: 60%
“…In addition, the P2X7, NLRP3, ASC, cleaved XIAP, caspase-11 and caspase-1 protein levels were declined in the BBG treated SCI animal model. Moreover, NLRP1 protein expression levels did not significantly differ among the SCI model groups and immunohistochemistry staining also illustrated that the NLRP3 and ASC protein expression levels were notably decreased in the BBG treated SCI animal model [125] . BBG administration can efficaciously reduce the pro-inflammatory factors including IL-1β and IL-18 expression levels after SCI.…”
Section: Inhibiting the Pyroptosis-regulated Cell Death And Inflammasmentioning
confidence: 84%
“…BBG is called a P2X7 receptor inhibitor, which notably enhances functional recoveries after SCI [123] , [124] . Zhou et al studied the potential effect of BBG on inflammasomes-related protein expression in SCI model [125] . The study also reported that the P2X7, NLRP3, ASC, cleaved XIAP, caspase-11 and caspase-1 expression levels were noticeably enhanced in the SCI animal group than the sham model group.…”
Section: Inhibiting the Pyroptosis-regulated Cell Death And Inflammasmentioning
confidence: 99%
“…In this regard, purinergic signaling is often associated with pain and inflammatory responses [ 29 ]. For instance, the purine molecule ATP has been demonstrated to play an important role in regulating nociceptive transmission in different regions of the spinal cord and brain, and promotes the release of mediators involving pain [ 12 , 30 , 31 ]. Therefore, targeting the specific receptors for ATP (e.g., P2X and P2Y) could be effective in modulating pain conditions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the purine molecule ATP plays a key role in the regulation of nociceptive transmission [ 11 ]. Notably, the P2X7 receptor (P2X7R) is an ATP-gated ion channel that plays an important role in the inflammatory response and in different pain states [ 12 , 13 ]. P2X7R is overactivated due to ATP release, resulting in anion imbalance and triggering of microglia, that additionally exacerbate cell damage [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%